Language learning and teacher education : a sociocultural approach - Hawkins, Margaret R., 1953- (Bilingual education and bilingualism, 2004)
Describes, theorizes and analyses language teacher education practices from a sociocultural perspective. Links teacher education practices with language teacher practices.